2022
DOI: 10.3389/fpsyg.2022.836461
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety and Subjective Quality of Life Among Chinese Left-Behind Children: The Mediating Role of Social Support

Abstract: The issue of left-behind children has become a key focus in China. In this study, we investigate the mediating role of social support between social anxiety and the subjective quality of life among left-behind children in China (N = 379, Mage = 13.65). A total of 710 junior high school students were recruited using clustering random sampling from five middle schools in China and investigated using the Social Anxiety Scale for Children, Social Support Rating Scale for Adolescents, and Inventory of Subjective Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“… Hindmarch (1998) found that anxious individuals will have cognitive biases and cannot perceive things correctly, which verified the deterioration model. Existing empirical research found that perceived social support can mediate the relationship between anxiety and life satisfaction ( Yu et al, 2020 ), quality of life ( Kugbey et al, 2020 ; Yang and Lu, 2022 ), and depression ( Dour et al, 2014 ). However, less research has been done on the relationship between SSA (as a component of social support) and anxiety or depression.…”
Section: Introductionmentioning
confidence: 99%
“… Hindmarch (1998) found that anxious individuals will have cognitive biases and cannot perceive things correctly, which verified the deterioration model. Existing empirical research found that perceived social support can mediate the relationship between anxiety and life satisfaction ( Yu et al, 2020 ), quality of life ( Kugbey et al, 2020 ; Yang and Lu, 2022 ), and depression ( Dour et al, 2014 ). However, less research has been done on the relationship between SSA (as a component of social support) and anxiety or depression.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, LBC who are the only children of the family tend to have greater expectations, leading to higher susceptibility to behavioral, mental, and even academic issues (Wang and Guo, 2010). LBC also tend to experience heavier social anxiety (Wu et al, 2019;Yang et al, 2022 ). Research on the separation of LBC also demonstrated that those who were left behind earlier in their life are more prone to depression and anxiety (Liu et al, 2009), with the impacts being greater when the mother migrates.…”
Section: Mental Health Of Lbcmentioning
confidence: 99%
“…Compared to non-left-behind children, left-behind children not only have less opportunity to get taught but also get less care fro their parents in the interpersonal skills aspect. Thus, their cooperation skills cultivate much slower and have more obstacles when learning it [10].…”
Section: On Cooperation Level Aspectmentioning
confidence: 99%